Pathology of Marek’s disease in layer chickens in Bangladesh (Bangladesh Veterinarian, 2018)
We performed a pathological investigation of Marek’s disease in commercial layer chickens in Bangladesh. A total of 23 dead or sick birds, suspected of Marek’s disease, were obtained from 10 different layer farms of Mymensingh, Gazipur, Tangail and Pabna districts from March to November 2011. Lameness, torticollis and paralysis were characteristic clinical signs in the affected birds. At necropsy, diffuse enlargement or nodular lesions were found in the liver, spleen, proventriculus, heart, kidney, ovary and intestine. The highest number of tumours were in the proventriculus (17/23) followed by liver (13/23) and spleen (8/23). No gross lesions were found in the nerve plexus. Histologically, lymphomatous lesions were observed. In the liver and kidney, diffuse proliferation of pleomorphic lymphocytes was associated with extensive damage of the parenchyma, while the lesions in the proventriculus and intestine were characterized by diffuse and focal and nodular proliferation of lymphocytes. The findings of the present study suggest that Marek’s disease can be expected without obvious nervous lesions and the lymphomatous lesions could be diverse depending on the tissues involved.Bangl. vet. 2017. Vol. 34, No. 2, 35-41